PENGARUH LABA AKUNTANSI DAN ARUS KAS TERHADAP RETURN SAHAM SYARIAH YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX TAHUN 2007-2008 - Widowati, Elvina (Jurnal Wahana Akuntansi, 2013)
Capital market is a financial institution, where investors can invest their funds in securities. Establishment of the Jakarta Islamic Index is expected to improve investor confidence to develop the investment in the securities of the sharia. The one of investing purpose is to get a return as an advantage. The information of earnings and cash flow may cause investors action toward the company’s stock. This study aims to determine the effect of accounting earnings and cash flow toward stock return. The data which used are secondary data such as companyâ€™s financial reports and stock prices. The population in this study are stocks listed in the Jakarta Islamic Index 2007-2008. The sample which used in this study are 32 companies. Technique of sampling that is used in this study is purposive sampling method. The data analysis that used is multiple regression analysis. The Regression analysis is used to test the effect of accounting earnings variable and cash flows variable toward stock returns. The analysis results shown that both independent variables have simultaneously influence to the dependent variable, and individually only accounting earnings influence significantly to the stock returns. Meanwhile, the total cash flow does not influence the stock return variable.Based on the results, the suggestion for further research is able to extend the period of observation, using other variables are not described in this study. Key Words: Accounting Earnings, Cash Flow, Stock Return, Jakarta Islamic Index